The Crucial Role of Bioenergy in a Climate‐Neutral Energy System in Germany. Issue 3 (23rd March 2022) - Lauer, Markus; Dotzauer, Martin; Millinger, Markus; Oehmichen, Katja; Jordan, Matthias; Kalcher, Jasmin; Majer, Stefan; Thraen, Daniela
Abstract: Greenhous gas mitigation requires urgent action, especially in transforming the energy system. Bioenergy is expected to counterbalance the variable power from wind and solar energy, but also for the de‐fossilization of the heat and transport sectors. This study assesses the wide range of options and evaluates the most cost‐efficient allocation of biomass for 95 % greenhouse gas emission reduction in the German energy system till 2050. The final state in 2050 shows bioenergy in different sectors, including pellet and woodchip boilers, bio‐based methane, different combined heat and power concepts, as well as liquid fuels, such as synthetic kerosene. Lignocellulosic biomass makes up the major proportion of future biomass options; however, appropriate strategies are needed to mobilize it. Abstract : The optimized role of bioenergy in a de‐fossilized energy system in Germany in 2050 is assessed. In this analysis, the total costs of 28 biomass supply chains were optimized and the relevant options information on greenhouse gas reduction costs is provided. The modeled bioenergy transformation is discussed with regard to the needs for its implementation.